'Candidatus Phytoplasma dypsidis', a novel taxon associated with a lethal wilt disease of palms in Australia. Issue 5 (18th May 2021) - Jones, Lynne M.; Pease, Bradley; Perkins, Sandy L.; Constable, Fiona E.; Kinoti, Wycliff M.; Warmington, David; Allgood, Ben; Powell, Sonya; Taylor, Pieter; Pearce, Ceri; Davis, Richard I.
Abstract : A phytoplasma was initially detected in Dypsis poivriana by nested and real-time PCR from the botanical gardens in Cairns, Queensland, Australia in 2017. Further surveys in the Cairns region identified phytoplasma infections in eight additional dying ornamental palm species ( Euterpe precatoria, Cocos nucifera, Verschaffeltia splendida, Brassiophoenix drymophloeodes, Burretiokentia hapala, Cyrtostachys renda, Reinhardtia gracilis, Carpoxylon macrospermum ), a Phoenix species, a Euterpe species and two native palms ( Archontophoenix alexandrae ). Analysis of 16S rRNA gene sequences showed that this phytoplasma is distinct as it shared less than 97.5 % similarity with all other ' Candidatus Phytoplasma' species. At 96.3 % similarity, the most closely related formally described member of the provisional ' Ca . Phytoplasma' genus was ' Ca . Phytoplasma noviguineense', a novel taxon from the island of New Guinea found in monocotyledonous plants. It was slightly more closely related (96.6–96.8 %) to four palm-infecting strains from the Americas, which belong to strain group 16SrIV and which have not been assigned to a formal ' Candidatus Phytoplasma' species taxon. Phylogenetic analysis of the 16S rRNA gene and ribosomal protein genes of the phytoplasma isolate from a dying coconut palm revealed that the phytoplasma represented a distinct lineage within the phytoplasma clade. As the nucleotide identity with other phytoplasmas is less than 97.5 % and the phylogenetic analyses show that it is distinct, a novel taxon 'Candidatus Phytoplasma dypsidis' is proposed for the phytoplasma found in Australia. Strain RID7692 (GenBank accession no. MT536195) is the reference strain. The impact and preliminary aspects of the epidemiology of the disease outbreak associated with this novel taxon are described.